Fine motor skills in a population of children in remote Australia with high levels of prenatal alcohol exposure and Fetal Alcohol Spectrum Disorder - Robyn Doney; Barbara R. Lucas; Rochelle E. Watkins; Tracey W. Tsang; Kay Sauer; Peter Howat; Jane Latimer; James P. Fitzpatrick; June Oscar; Maureen Carter; Elizabeth J. Elliott (BMC, 2017)
Abstract Background Many children in the remote Fitzroy Valley region of Western Australia have prenatal alcohol exposure (PAE). Individuals with PAE can have neurodevelopmental impairments and be diagnosed with one of several types of Fetal Alcohol Spectrum Disorder (FASD). Fine motor skills can be impaired by PAE, but no studies have developed a comprehensive profile of fine motor skills in a population-based cohort of children with FASD. We aimed to develop a comprehensive profile of fine motor skills in a cohort of Western Australian children; determine whether these differed in children with PAE or FASD; and establish the prevalence of impairment. Methods Children (n = 108, 7 to 9 years) were participants in a population-prevalence study of FASD in Western Australia. Fine motor skills were assessed using the Bruininks-Oseretsky Test of Motor Proficiency, which provided a Fine Motor Composite score, and evaluated Fine Manual Control (Fine Motor Precision; Fine Motor Integration) and Manual Coordination (Manual Dexterity; Upper-Limb Coordination). Descriptive statistics were reported for the overall cohort; and comparisons made between children with and without PAE and/or FASD. The prevalence of severe (≤ 2nd percentile) and moderate (≤16th percentile) impairments was determined. Results Overall, Fine Motor Composite scores were 'average' (M = 48.6 ± 7.4), as were Manual Coordination (M = 55.7 ± 7.9) and Fine Manual Control scores (M = 42.5 ± 6.2). Children with FASD had significantly lower Fine Motor Composite (M = 45.2 ± 7.7 p = 0.046) and Manual Coordination scores (M = 51.8 ± 7.3, p = 0.027) than children without PAE (Fine Motor Composite M = 49.8 ± 7.2; Manual Coordination M = 57.0 ± 7.7). Few children had severe impairment, but rates of moderate impairment were very high. Conclusions Different types of fine motor skills should be evaluated in children with PAE or FASD. The high prevalence of fine motor impairment in our cohort, even in children without PAE, highlights the need for therapeutic intervention for many children in remote communities.